2005
DOI: 10.1016/j.jacc.2004.10.079
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Shear-Induced Platelet Aggregation in Patients Who Experience Subacute Stent Thrombosis

Abstract: Shear-induced platelet aggregation is increased in patients experiencing SAT compared with controls receiving dual antiplatelet therapy and to normals receiving no antiplatelet therapy, which suggests increased intrinsic patient-related platelet reactivity in patients with SAT. The predictive value of SIPA for SAT requires prospective investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
86
0
3

Year Published

2006
2006
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(92 citation statements)
references
References 19 publications
3
86
0
3
Order By: Relevance
“…Platelet function tests have been used to monitor patient response to antiplatelet therapy [34]. Several studies suggest that low responsiveness to antiplatelet therapy, as measured in various platelet-function tests, correlates with high rates of incidences of ischemic events [34][35][36][37]. However, it is questionable whether the resistance defined by various platelet-function tests is actually paralleled by the occurrence of adverse clinical events.…”
Section: Discussionmentioning
confidence: 99%
“…Platelet function tests have been used to monitor patient response to antiplatelet therapy [34]. Several studies suggest that low responsiveness to antiplatelet therapy, as measured in various platelet-function tests, correlates with high rates of incidences of ischemic events [34][35][36][37]. However, it is questionable whether the resistance defined by various platelet-function tests is actually paralleled by the occurrence of adverse clinical events.…”
Section: Discussionmentioning
confidence: 99%
“…This may explain why stent thrombosis occurs only in selected patients after clopidogrel withdrawal. The observation that patients with diabetes frequently have suboptimal response to aspirin may also be implicated in their increased thrombotic event rate, which has been invoked as a potential mechanism leading to stent thrombosis occurring even after 1 year of clopidogrel treatment (21)(22)(23)(24)(25). Several mechanisms lead to reduced responsiveness to aspirin and increased platelet reactivity in diabetic patients, including increased platelet exposure to ADP (21).…”
Section: Discussionmentioning
confidence: 99%
“…The prognostic implications associated with increased platelet reactivity and enhanced inflammatory status, which include progression of atherosclerotic disease and atherothrombotic complications, underscores the potential clinical impact of these functional findings (23)(24)(25)(35)(36)(37)(38)(39). The influence of clopidogrel on inflammatory markers and platelet biomarkers and how these may affect long-term clinical outcomes is currently being evaluated in a large-scale randomized clinical trial.…”
Section: Discussionmentioning
confidence: 99%
“…10 However, discrepancy exists as to whether clopidogrel resistance correlates with stent thrombosis. In a study of 23 patients, Wenaweser et al found that aspirin and clopidogrel resistance, but not clopidogrel resistance alone, predicted a history of stent thrombosis.…”
Section: Discussionmentioning
confidence: 99%